Statistical optimization and inequality assessment of corn planting: an analysis of seeding depth and spacing uniformity - Aryal, Bhaskar Upadhyay (Kansas State University, 2024)
Sowing is a fundamental planting operation in a growing season, and its primary purpose is to consistently place the seed at a target depth with uniform spacing. Both seeding depth and plant-to-plant spacing are key factors that govern the success of crop establishment in corn. Inappropriately positioned seeds can lead to poor seedbed conditions significantly influencing crop establishment and substantially reducing yield potential. Modern planters are designed to effectively singulate and precisely position seeds in a furrow ensuring adequate seed-to-soil interaction. Inclement weather conditions often limit planting windows, and higher planting speed is one of the management strategies farmers resort to for compensation. However, such interplay of planter operation settings can result in sub-optimal seeding depth and variable spacing, leading to poor agronomic outputs. The purpose of this study was twofold: first to identify the optimal operational parameters for a row crop planter that consistently achieves target seeding depth. Second, to assess the impact of such parameters on within-row spacing variability and evaluate yield disparities. Field experiments were conducted in a split-plot arrangement with downforce levels ranging from 100—325 lbf and planting speeds spanning from 5—10 mph. A second-order full-quadratic model was defined, and a face-centered central composite design was employed to evaluate the relationship between seeding depth and operation parameters—downforce and speed. Spacing variability was studied using metrics based on distribution moments as well as the Gini index and Lorenz curves. The impact of spacing inequality on yield outcomes at a plant level was quantified with regression techniques. Analysis reveals distinct downforce and speed requirements across sections of a planter—track, non-track, and wing. Intermediate planting speed (7.1—7.5 mph) coupled with moderate downforce level (222—232 lbf) yielded minimal bias from the target seeding depth (2 in.) in non-track and wing sections. The track section minimized bias at a relatively lower planting speed and downforce level. Lower planting speeds coupled with moderate downforce settings minimized spacing inequality as evidenced by lower G-spacing values, and relatively minimal deviations in Lorenz curves. Yield outcome at the plant level was negatively and significantly (α=0.05) correlated with within-row variability of corn plant spacing. For each unit increase in plant spacing variation, a reduction of 9.13 g per plant was observed. Other non-ideal spacing outcomes like missing plants and multiples also negatively impacted corn yield. Findings indicate a direct influence of operation settings—planting speed and applied downforce, on seeding depth as well as spacing uniformity. The influence on spacing uniformity, in turn, translates to a significant impact on corn yield. The extent of yield loss is accentuated as inequality in spacing rises. These insights underscore the need for prudent management of operational settings.
Keywords: Seeding depth; Plant spacing; Response surface methodology; Lorenz curves; Planters